Why do lipid nanoparticles target the liver? Understanding of biodistribution and liver-specific tropism - Hosseini-Kharat, Mahboubeh; Bremmell, Kristen E.; Prestidge, Clive A. (Molecular therapy. Methods & clinical development, 2025)
Lipid nanoparticles (LNPs) are now highly effective transporters of nucleic acids to the liver. This liver-specificity is largely due to their association with certain serum proteins, most notably apolipoprotein E (ApoE), which directs them to liver cells by binding to the low-density lipoprotein (LDL) receptors on hepatocytes. The liver’s distinct anatomy, with its various specialized cell types, also influences how LNPs are taken up from the circulation, cleared, and how effective they are in delivering treatments. In this review, we consider factors that facilitate LNP’s effective liver targeting and explore the latest advances in liver-targeted LNP technologies. Understanding how LNPs are targeted to the liver can help for effective design and optimization of nanoparticle-based therapies. Comprehension of the cellular interaction and biodistribution of LNPs not only leads to better treatments for liver diseases but also delivers insight for directing nanoparticles to other tissues, potentially broadening their range of therapeutic applications. [Display omitted] Lipid nanoparticles (LNPs) preferentially accumulate in the liver through ApoE-mediated LDL receptor binding. This review examines this specificity and explores strategies to enhance targeting, expanding LNP applications beyond hepatic diseases.